Pramipexole Upregulates Dopamine Receptor D2 and D3 Expression in Rat Striatum - Naohito Tokunaga; Mohammed Emamussalehin Choudhury; Noriko Nishikawa; Masahiro Nagai; Tomoaki Tujii; Hirotaka Iwaki; Mika Kaneta; Masahiro Nomoto (Elsevier, 2012)
Randomized clinical trials have shown that pramipexole has an antidepressant effect in patients with Parkinson's disease. We investigated the comparative efficacy of pramipexole toward dopamine receptor D2 and D3 expression in rat brain. Groups of rats were treated subacutely with pramipexole (1 mg/kg), imipramine (10 mg/kg), or bromocriptine (5 mg/kg), with appropriate controls. Using real-time RT-PCR and immunoblotting, dopamine receptor D2 and D3 expression was up-regulated in the striatum following pramipexole treatment, while imipramine and bromocriptine had no significant effects. These findings support that pramipexole exerts additional therapeutic benefits such as decreasing depression by increasing dopamine receptor D3 expression in the striatum. Keywords:: dopamine receptor, Parkinson's disease, pramipexole